2021
DOI: 10.3390/molecules26040819
|View full text |Cite
|
Sign up to set email alerts
|

Myrtus communis Essential Oil; Anti-Parasitic Effects and Induction of the Innate Immune System in Mice with Toxoplasma gondii Infection

Abstract: Background: Myrtus communis (M. communis) is a wild aromatic plant used for traditional herbal medicine that can be demonstrated in insecticidal, antioxidant, anti-inflammatory, and antimicrobial activity of its essential oils (MCEO). Aim: The present study aimed to evaluate the prophylactic effects of M. communis essential oil (MCEO) against chronic toxoplasmosis induced by the Tehran strain of Toxoplasma gondii in mice. Methods: Gas chromatography/mass spectrometry (GC/MS) analysis was performed to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Similar to most previous surveys ( Ranasinghe et al., 2013 ; Rahayu et al., 2021 ), we reported the presence of flavonoids, tannins, alkaloids, terpenoids, and saponins in CZME and cinnamaldehyde, trans-cinnamyl acetate, and trans-ethyl p-methoxycinnamate as the most abundant constituents of CZME by GC/MS analysis. Nevertheless, it has been supported several times that the chemical composition of plants may be influenced by factors such as the place and time of harvest, the part of the plant used for analysis, and the method of essential oil extraction ( Masoumi-Ardakani et al., 2016 ; Shaapan et al., 2021 ). Cinnamaldehyde is the main compound of CZME and has a broad range of medicinal and pharmacological applications such as anticancer, cardio-protection, anti-inflammatory, antibacterial, antifungal, and anti-parasitic activities ( Chen et al., 2017 ; Doyle and Stephens, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to most previous surveys ( Ranasinghe et al., 2013 ; Rahayu et al., 2021 ), we reported the presence of flavonoids, tannins, alkaloids, terpenoids, and saponins in CZME and cinnamaldehyde, trans-cinnamyl acetate, and trans-ethyl p-methoxycinnamate as the most abundant constituents of CZME by GC/MS analysis. Nevertheless, it has been supported several times that the chemical composition of plants may be influenced by factors such as the place and time of harvest, the part of the plant used for analysis, and the method of essential oil extraction ( Masoumi-Ardakani et al., 2016 ; Shaapan et al., 2021 ). Cinnamaldehyde is the main compound of CZME and has a broad range of medicinal and pharmacological applications such as anticancer, cardio-protection, anti-inflammatory, antibacterial, antifungal, and anti-parasitic activities ( Chen et al., 2017 ; Doyle and Stephens, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A vital mechanism that plays an essential role in the prevention and even control of toxoplasmosis is the reinforcement of the immune system, especially cellular immunity, by increasing some inflammatory factors and mediators ( Sasai et al., 2018 ). Due to having certain compounds, medicinal herbs have recently displayed promising in vitro and in vivo anti- Toxoplasma and anti- T. gondii effects with immunomodulation of animals and host cells ( Teixeira et al., 2020 ; Shaapan et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many medicinal effects of Myrtus communis L. have been mentioned in the literature [3][4][5][6][7]. In addition, there are studies showing the antiparasitic effect of Myrtus communis L. In a study, potent prophylactic effects of essential oils of Myrtus communis L. were shown in mice infected with Toxoplasma gondii, especially at doses of 200 and 300 mg/kg [19]. Another study was carried out on promastigote and amastigote forms of Leishmania tropica and it was shown that the essential oils of Myrtus communis L. significantly inhibited their growth in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…e attained essential oil was then dehydrated by over anhydrous sodium sulfate and kept in darkness at 4 °C in glass tubes until testing [21].…”
Section: Preparing Essential Oilmentioning
confidence: 99%